Pengaruh Inflasi, Nilai Tukar, Ekspor dan Impor Terhadap PDB di Negara BELGIA - Favian Ardine Agathon; Eni Setyowati; Didit Purnomo; Maulidyah Indira Hasmarini (Economics and Digital Business Review, 2024)
At both current and constant prices, the Gross Domestic Product (GDP) is used as an indicator to determine a nation's economic condition during a given time period. The goal of this study is to look at how inflation, exchange rates, exports, and imports affected Belgium's economic growth between 2002 and 2022. The strategy utilized in this study is different straight relapse with the Normal Least Square (OLS) technique. Information on Gross domestic product, expansion, trade rates, commodities and imports were taken from the Worldbank. The outcomes showed that the commodity variable affects Belgium's monetary development. Import factors significantly affect Belgium's financial development. In the interim, expansion and conversion scale factors significantly affect Belgium's monetary development.